Rabies - Hong, Angela; Kylas, Anya (The Meducator, 2024)
Rabies is a lethal zoonotic disease responsible for the deaths of 60,000 people annually. Rabies virus (RABV) is a lyssavirus prototype with a mortality rate of nearly 100% after symptom onset. Following an incubation period of 1-3 months after exposure, hosts develop encephalitis leading to two possible symptomatologies. A clinical presentation of RABV is encephalitic rabies, characterised by hydrophobia, agitation, and hypersalivation. Alternatively, RABV may also present as paralytic rabies, characterised by muscle weakness and paralysis. Both types eventually result in a comatose state followed by death. Despite mass vaccination campaigns in developing nations aiming to reduce infection across mammalian populations, the virus continues to gain prevalence in novel species and geographic areas, proving to be a threat of increasing magnitude.